Direct Observations of Nanofilament Evolution in Switching Processes in HfO2 -Based Resistive Random Access Memory by In Situ TEM Studies - Li, Chao (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.